Control System for Pakcoy Hydroponic Cultivation with Nutrient Film Technique based on Internet of Things - Aisyah, Putri Yeni; J.A.S, Pankrasius Iubilaeum; Ainin, Qurrotu; Wijayanti, Monica Intan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
When applying the hydroponic method, there are several main factors that need to be looked at, such as nutrition and pH. This research involves the design of a Nutrient and pH Monitoring and Control System for Hydroponic Plants Based on the Internet of Things (IoT) with closed loop control. This system aims to make it easier for farmers to manage their crops in all conditions by monitoring nutritional needs, pH levels and overall plant health from anywhere using a smartphone. Based on research that has been carried out, the Total Dissolved Solid (TDS) sensor shows an accuracy of up to 99.3%, with an error margin of 2.43% and a correction value of 2.43 ppm. The pH sensor has an accuracy of up to 99.35%, with an error of 0.039%, and a correction of 0.039. The JSN-04 ultrasonic sensor has an accuracy of up to 100%, with 0% error, and 0 cm correction. In plants that are cultivated using a control system, the height gain is more significant than plants without a control system.